Horolezecký slang ve společenském kontextu - Slezáková, Jitka (Lidé města, 2003)
The first viewpoint in slang research is linguistic. The second one, which is taken into account here, is sociolinguistic. The article is based on the research conducted in 1998 and 1999 with the method of inquiry, long-term participating observation and excerption from expert periodicals. lnquiry was carried out not only among climbers but also among general public and students of the Faculty of Physical Training at the Charles University. People using climbing slang try to demonstrate through their speech their allegiance to the hobby group and enter into socio-relation of this group. For each member, the process of integratian also means to learn climbing vocabulary and idioms. According to the extent and character of the vocabulary used we can estimate how long a sportsman has been practicing the climbing. First of all he picks up expressions of actions, activities and situations, starting with easier and general words and proceeding towards more difficult, special and expressive ones. Later on his speech comes to be spontaneous and creative. lmportant role in this process plays the team of co-climbers. In this society (e.g. sportclubs), the variety of individual speech originates.